The Effect of CO2 on Resting-State Functional Connectivity: Isocapnia vs. Poikilocapnia - McKetton, Larissa; Sam, Kevin; Poublanc, Julien; Crawley, Adrian P.; Sobczyk, Olivia; Venkatraghavan, Lakshmikumar; Duffin, James; Fisher, Joseph A.; Mikulis, David J. (Frontiers in Physiology, 2021)
The normal variability in breath size and frequency results in breath-to-breath variability of end-tidal PCO2 (PETCO2), the measured variable, and arterial partial pressure of carbon dioxide (PaCO2), the independent variable affecting cerebral blood flow. This study examines the effect of variability in PaCO2 on the pattern of resting-state connectivity. A ROI-to-ROI and Seed-to-Voxel first-level bivariate correlation, hrf-weighted analysis for measuring rsMRI connectivity was performed during two resting-state conditions: (a) normal breathing associated with breath-to-breath variation in PaCO2 (poikilocapnia), and (b) normal breathing with breath-to-breath variability of PETCO2 dampened using sequential rebreathing (isocapnia). End-tidal PCO2 (PETCO2) was used as a measurable surrogate for fluctuations of PaCO2. During poikilocapnia, enhanced functional connections were found between the cerebellum and inferior frontal and supramarginal gyrus, visual cortex and occipital fusiform gyrus; and between primary visual network and the hippocampal formation. During isocapnia, these associations were not seen, rather enhanced functional connections were identified in the corticostriatal pathway between the putamen and intracalacarine cortex, supracalcarine cortex and precuneus cortex. We conclude that vascular responses to variations in PETCO2, account for at least some of the observed resting state synchronization of BOLD signals.